Communicating Care in Coastal Fisheries: Restoration, Adaptation, and Collaborative Policy Change - McGreavy, Bridie; Hillyer, Gabrielle; Joyce, Jessica; Farr, Emily; Lauer, B; Sutton, Anthony; Moody, Katie; Batchelder, Jessica; Jayamaha, Ishani; McMahan, Marissa (Maine Policy Review, 2023)
The soft-shell clam fishery in Maine and Wabanaki homelands is in a state of crisis, or so say most news reports about this fishery. While there is ample evidence that small-scale fisheries and the communities these fisheries support are rapidly changing, the crisis narrative conceals more than it reveals about how communities are actively responding and the longer-term histories to which these changes are connected. In this paper, we describe the dominance of the crisis narrative in news reports about clamming and we connect with critiques in Native American and Indigenous Studies and environmental communication that describe some of the problems with this narrative. These critiques also point to a need to shift from crisis to more relational forms of care. When we make this shift, different stories of conservation and intertidal restoration, the emergence of partnership networks, and the formation of collaborative policy solutions come into view. We listen to and share these stories and we conclude by asking how listening, as a call to action, can shape broader, crisis-focused efforts and encourage practices of care within climate adaptation planning across contexts.
Keywords: Clam fishery; crisis; news media; care; intertidal restoration; collaborative policy